Construction and the Process of Implementing the Management Control System in a Local Self-Government Unit – a Practical Approach - Bartoszewicz, Anna (Olsztyn Economic Journal, 2016)
Since 1 January 2010, management control has been functioning in the units of the public finance sector as it has replaced the previously applied financial control. The assumption of management control was to support the achievement of the objectives and performance of tasks carried out by public entities in Poland and consequently to facilitate the process of managing them. As practice shows, some entities have failed to develop an adequate system of action that would allow making a good use of this tool. Thus, the purpose of this article is to present a practical approach to the deployment and implementation of a management control system in a local government unit and indicate substantive gaps that remain. The article presents an exemplary solution of the deployment and implementation of a management control system operating in one of the district offices in Poland. The article also presents implications resulting from the functioning of this system and gives a critical approach to the subject matter, pointing out shortcomings in the functioning of management control in a public entity.